Up-to-the-Minute Privacy Policies via Gossips in Participatory Epidemiological Studies - Sharma, Aakash; Nilsen, Thomas Bye; Czerwinska, Katja Pauline; Onitiu, Daria; Brenna, Lars; Johansen, Dag; Johansen, Håvard D. (Frontiers in Big Data, 2021)
Researchers and researched populations are actively involved in participatory epidemiology. Such studies collect many details about an individual. Recent developments in statistical inferences can lead to sensitive information leaks from seemingly insensitive data about individuals. Typical safeguarding mechanisms are vetted by ethics committees; however, the attack models are constantly evolving. Newly discovered threats, change in an individual's perception or the law can lead to concerns that affect the study. Addressing these concerns is imperative to maintain trust with the researched population. We are implementing Lohpi as an infrastructure for building accountability in data processing for participatory epidemiology. We address the challenge of data-ownership by allowing institutions to host data on their managed servers while being part of the Lohpi. We update data access policies using gossips. We present Lohpi as a novel architecture for research data processing and evaluate the dissemination, overhead, and fault-tolerance.